(3GdJGQjN GdLGeYs - (3dWa Gddg Hf CMeO Hf dWa Gddg Hf CMeO LMGa,J (B1243 (3g` s
(3ChdgG (B:s
(3hONdJ SfI (B1095: (3hajgG Jhai GdMSjf Hf CMeO jhe GdLeYI ZQI QHjY GdBNQ heGRGd HgPG GdYGe jQSd GdSjO eMeO GdZQHGfi (B( (3Ydi (B) (3GdEeGe hjcKQ GdEYJQGV Ydi GdRjha ef GdOQGge , aJVQQ GdfGS dPdc s
(3BNQgG (B:s
(3hai djdI GdQHhY SGOS YTQ (B( (3ef (B) (3ThGd SfI (B1231 (3g` , cGfJ OYZhI ehdGfG CejQ GdeDefjf SjO GdeSdejf hCMVQ GdfGS ddOQS HGdbHI JMJ GdOGQ hGdJaJ GdYGeI hGdNGUI , hGROMe GdfGS CTO GdEROMGe heGRGdhG jbOehf Edi ebGeI ddHjYI HGdbUQ s
(3HgG fXGe GdJYbjHIs
(3Jee Hg GdeDda (B: (3CfHGA GdRef ai JGQjN Gdjef (B" (3Edi NdGaI GdegOi YHO Gddgs
(3cJHJ Hbde bdjd GdfbWs
(3hJYGhQ YdjgG CcKQ ef fGSN s
(3hChQGbgG eVWQHI GdJQJjH s
(3HHYV ChQGbgG JbWjY hWeS s
Keywords: (3GdJGQjNs